A multiyear cross‐sectional study of U.S. national prescribing patterns of first‐generation sedating antihistamines in older adults with skin disease. (21st July 2019) - Cenzer, I.; Nkansah‐Mahaney, N.; Wehner, M.; Chren, M.M.; Berger, T.; Covinsky, K.; Berger, K.; Abuabara, K.; Linos, E.
Summary: Background: First‐generation antihistamines (FGAs) are classified as 'potentially inappropriate' for use in older patients (patients aged ≥ 65 years). However, the prevalence of and factors associated with FGA prescription have not been studied. Objectives: To examine FGA prescription rates for older patients who visited dermatology offices, and compare them to those for younger patients (patients aged 18–65 years) who visited dermatology offices and those for older patients who visited primary‐care physicians (PCPs). Methods: This was a multiyear cross‐sectional observational study using data from the U.S. National Ambulatory Medical Care Survey (2006–2015). Visits by patients aged 18 years or older were included in the study; the data comprised 15 243 dermatology office visits and 66 036 PCP office visits. The main outcome was FGA prescription. Other variables included physician specialty (dermatologist or PCP), patient's age, diagnosis of dermatological conditions and reason for visit. Results: For dermatology visits, the overall FGA prescription rate for older patients was similar to that for younger patients (1·5% vs. 1·2%; P = 0·19), even when the diagnosis was dermatitis or pruritus (3·7% vs. 4·8%; P = 0·21) or when itch was a complaint (7·6% vs. 6·7%; P = 0·64). However, the rate of FGA prescription for dermatology visits was lower than that for PCP visits, in analyses matched for patient and visit characteristics (3·9% vs. 7·4%; P = 0·02). Conclusions: Our findings suggest that FGAs are overprescribed to older patients but that dermatologists are less likely to prescribe FGAs than PCPs. What's already known about this topic? First‐generation antihistamines (FGAs) have been shown to pose substantial risks to older adults, including cognitive impairment, falls, confusion, dry mouth and constipation. Therefore, FGAs have been classified as 'potentially inappropriate' for use in older patients by the American Geriatrics Society. It has also been shown that dermatologists do not always take patient characteristics (e.g. age or life expectancy) into account when deciding on a treatment, instead following a 'one‐size‐fits‐all' approach. What does this study add? FGAs are often prescribed during dermatology visits, and prescription rates do not differ between older and younger patients. There were no significant differences in prescription rates when comparing younger and older adults with the same diagnosis or symptom (e.g. dermatitis, pruritus or itch). FGAs are prescribed at higher rates in primary‐care offices than in dermatology offices. Abstract : Linked Comment: Mate. Br J Dermatol 2020; 182 :541 . Respond to this article